Etv4 regulates nociception by controlling peptidergic sensory neuron development and peripheral tissue innervation - Rios, Antonella Soledad (2022)
The perception of noxious environmental stimuli by nociceptive sensory neurons is an essential mechanism for the prevention of tissue damage. Etv4 is a transcriptional factor expressed in most nociceptors in dorsal root ganglia (DRG) during the embryonic development. However, its physiological role remains unclear. Here, we showthat Etv4 ablation results in defects in the development of the peripheral peptidergic projections in vivo, and in deficits in axonal elongation and growth cone morphology in cultured sensory neurons in response to NGF. From a mechanistic point of view, our findings reveal that NGF regulates Etv4-dependent gene expression of molecules involved in extracellular matrix (ECM) remodeling. Etv4-null mice were less sensitive to noxious heat stimuli and chemical pain, and this behavioral phenotype correlates with a significant reduction in the expression of the pain-transducing ion channel TRPV1 in mutant mice. Together, our data demonstrate that Etv4 is required for the correct innervation and function of peptidergic sensory neurons, regulating a transcriptional program that involves molecules associated with axonal growth and pain transduction.